Friendship of stock market indices: A cluster-based investigation of stock markets - László Nagy; Mihály Ormos (Journal of Risk and Financial Management, 2018)
This paper introduces a spectral clustering-based method to show that stock prices contain not only firm but also network-level information. We cluster different stock indices and reconstruct the equity index graph from historical daily closing prices. We show that tail events have a minor effect on the equity index structure. Moreover, covariance and Shannon entropy do not provide enough information about the network. However, Gaussian clusters can explain a substantial part of the total variance. In addition, cluster-wise regressions provide significant and stationer results.
Keywords: 330; cluster analysis; equity index networks; machine learning